Youth In/Activity determining the youth’s landscape perception of UP Diliman spaces conducive for green exercise through gamification - Capalad, Patrick Carl T. (College of Architecture, University of the Philippines Diliman, 2023)
Inactivity is prevalent in our cities. Urbanization and our growing disconnect with nature and the outdoors are linked with a higher risk of health problems, both physical and mental. The youth population is at risk, with a high prevalence of inactivity and sedentary behaviors among the Filipino youth. Green exercise is the synergy between nature exposure and physical activity. Being relatively low cost and with evidence of positive benefits, it is a sustainable health intervention option. The research investigates landscape perception for green exercise with the youth as the target demographic. However, with the modern lifestyle of youth being characterized by technology, social media, mass media, and gaming - how can we bridge the gap between youth and the outdoors? A concept gaining traction for its ability to motivate, retain, and positively influence human behavior - gamification or the application of game elements to traditionally non-game settings or contexts - like landscape perception research, was employed. This was integrated into the landscape and perception methodology through the creation of a gamified toolkit, utilizing game elements to achieve the research objectives. Using online, on-site, and gamified data gathering methods, the study was able to identify, compare, and contrast the in/active youth's perception, interaction, and movement across the urban green spaces of UP Diliman. The methods and findings were synthesized into a proposed Green Exercise App that aims to scale up the landscape perception methodology and promote green exercise to urban youth through a gamified landscape experience.